Genetic variability and inter-relation of seed yield with contributing traits in Indian mustard (Brassica juncea) - HS Meena,; Arun Kumar,; VV Singh,; PD Meena,; Bhagirath Ram,; Swarnim Kulshrestha, (Journal of Oilseed Brassica, 2026)
The experiments were conducted involving thirty nine genotypes of Indian mustard including 28 F1 crossesand 11 parental genotypes during Rabi 2014-15 to 2015-16 at ICAR-Directorate of Rapeseed-MustardResearch, Bharatpur, India. Analysis of variance on 12 quantitative characters was carried out which revealedconsiderable amount of genetic variability in genotypes for all the traits. The mean, range, genotypic coefficientof variation (GCV), phenotypic coefficient of variation (PCV), heritability in broad sense and genetic advancewere calculated. High genetic advance (GA %) coupled with high heritability for seed yield, 1000-seedweight, siliqua length, plant height and number of primary branches/ plant indicated the effectiveness ofselection for these traits. 1000-seed weight, siliqua length, plant height, main shoot length and days to maturitywere positively associated with seed yield; hence the selection for these traits would help in improving theseed yield. The crosses NRCHB 101 x NPJ 112, (NPJ 112 x RRN 727) x RH 406 and NPJ 112 x RRN 727revealed high mean performance for seed yield can be advanced for yield improvement and selection ofsuperior genotypes.